Pengaruh Penerapan Reward and Punishment terhadap Kinerja Pegawai dan Dampaknya terhadap Kinerja PDAM Tirta Intan Garut - Rohimat Nurhasan (Fakultas Ekonomi Universitas Garut, 2016)
This study aims to identify the effect of implementing reward and punishment on employee performance and its impact on the performance of PDAM Tirta Intan Garut. The research method used in this research is descriptive and verification methods. The respondents in this study were 70 people who were employees of PDAM Tirta Intan Garut. With the census method in determining the research sample. The data collection method in this research is by distributing questionnaires. The analysis technique in this research is validity and reliability test. The data analysis used in this research is descriptive analysis and path analysis with the help of Microsoft Excel and SPSS. 20. The results of this research show that the reward and punishment variable has a significant effect on employee performance, the employee performance variable has a significant effect on company performance, the reward and punishment variable has a